Association of advanced oxidative and adsorptive processes for dye treatment in the sanitizer industry: kinetic, equilibrium and toxicity evaluation - Napoleão, Daniella Carla; Gonçalves, Tássia Santos; Neves, Naiana Santos da Cruz Santana; Cavalcanti, Vanessa de Oliveira Marques; Silva, Marina Gomes; Santana, Ingrid Larissa da Silva; Santana, Rayany Magali da Rocha; Lucena, Alex Leandro Andrade de; Nascimento, Graziele Elisandra do (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
The presence of dyes in wastewater can cause several damages to the environment. Aiming at its removal, advanced oxidative processes (AOP) and adsorption (ADS) have been used. In this work, the removal of acid blue dye 80 (AA80) by AOP (photoperoxidation (PP) and photo-Fenton (PF)) and by ADS was evaluated, individually and combined. The use of the PP/UV-C system led to degradations of 72.7 and 83.8% for the λ of 334 and 622 nm, respectively. The PP/LED system did not degrade. For the PF process, > 90% degradation was obtained for both radiations. The [Fe] (1 mg.L-1) and [H2O2] (90 mg.L-1)were optimized for the PF/LED system. As for the PF/UV-C system, the optimal [H2O2] was 60 mg.L-1. The experimental data fit well with the Chan and Chu (2003) kinetic model with R2>0.94. The kinetic data showed a better fit to the pseudo-second order model (R2>0.90), while equilibrium was reached in 30 min with removal of 62.45 (λ=334 nm) and 83.22% (λ=622 nm), being well represented by the Langmuir and Sips models. Finally, the combined study promoted a 7% increase in AA80 removal, achieving an improvement in the final toxicity of the treated matrix when compared to isolated AOP systems.